Sex Scandal : The Private Parts of Victorian Fiction - Cohen, William A. (Book collections on Project MUSE., 1996)
In narratives ranging from Great Expectations to the Boulton and Park sodomy scandal of 1870-71, from Eliot's and Trollope's novels about scandalous women to Oscar Wilde's writing and his trials for homosexuality. Cohen shows how, in each instance, sexuality appears couched in coded terms. He identifies an assortment of cunning narrative techniques used to insinuate sex into Victorian writing, demonstrating that even as such narratives air the scandalous subject, they emphasize its unspeakable nature. Written with an eye toward the sex scandals that still whet the appetites of consumers of news and novels, this work is suggestive about our own modes of imagining sexuality today and how we arrived at them.